Effect of solid content and composition of hydroxypropyl methylcellulose–lipid edible coatings on physico-chemical and nutritional quality of ‘Oronules’ mandarins - Contreras-Oliva, Adriana; Rojas-Argudo, Cristina; Pérez-Gago, María B. (Wiley, 2019)
BACKGROUND: Citrus fruit represent an important source of vitamin C, as well as other bioactive compounds. Edible coatings have the potential to extend shelf life of citrus by providing a semi-permeable barrier to water and gases, which depends on coating composition, solid content (SC), and cultivar. However, little is known about the effect of coatings on citrus nutritional quality. This work studies the effect of coating composition and SC of hydroxypropyl methylcellulose (HPMC)–beeswax (BW)–shellac coatings on the physico-chemical, sensory and nutritional quality of ‘Oronules’ mandarins. Coatings prepared at the same lipid content differed in the BW: shellac ratio (1 : 3 and 3 : 1) and SC of the formulations (40 and 80 g kg−1). RESULTS: The coating with 1 : 3 BW: shellac ratio and 80 g kg−1 SC was the most effective controlling weight loss, although it was less effective than the commercial wax tested. Increasing SC had a greater effect than the BW: shellac ratio in fruit internal atmosphere and sensory quality, with the presence of off-flavour when coatings were applied at 80 g kg−1 SC. Nutritional quality was not affected by the application of the different treatments. CONCLUSION: HPMC–lipid coatings have the potential to extend shelf life of ‘Oronules’ mandarins. However, care should be taken controlling formulation SC to avoid the build-up of off-flavour.